Effect of temperature on the pores growth in the polycrystalline films of fusible metals - Dukarov, S.V.; Petrushenko, S.I.; Sukhov, V.N.; Churilov, I.G. (ННЦ "Харьковский физико-технический институт", 2014)
The paper presents the results of study through porosity in polycrystalline films of lead, tin and indium deposited on amorphous carbon substrate. It is established that the heating of film exponentially increases of the average size of through pores and do not leads to an increase of their concentration, which is practically independent of the temperature until to the melting point. We have determined the activation energy of the surface self in the films of these metals. Приведены результаты исследования сквозной пористости в поликристаллических плёнках свинца, олова и индия, напыленных на аморфные углеродные подложки. Установлено, что нагрев плёнок вызывает экспоненциальное увеличение среднего размера сквозных пор и не приводит к увеличению их концентрации, которая практически не зависит от температуры вплоть до температуры плавления. Определена энергия активации поверхностной самодиффузии в плёнках этих металлов.
Влияние температуры на рост пор в поликристаллических плёнках легкоплавких металлов
Ссылка на статью на русском языке: Дукаров С.В., Петрушенко С.И., Сухов В.Н., Чурилов И.Г. / Влияние температуры на рост пор в поликристаллических плёнках легкоплавких металлов // Вопросы атомной науки и техники. – 2014. – № 1(89) . – С.110–114
Keywords: Thin films; pore; self-diffusion; size effect